The Effect of Literacy-Based Play Activities to Improve Early Childhood Language Skills - Daffa, Muhammad (JURNAL PENA PAUD, 2024)
Developing linguistic competence during the formative years is critical for subsequent academic achievement, and targeted interventions can help children realize their maximum abilities. This investigation sought to evaluate the effects of literacy-oriented play activities on the linguistic abilities of children aged 4 to 6 years. The methodological approach employed was quasi-experimental, using a one-group pretest-post-test framework. The demographic focus of the study consisted of kindergarten children, with a purposively selected sample of 30 participants. Findings indicated a statistically significant improvement in the children's language abilities, evidenced by an average pretest score of 63.5 compared to a post-test score of 78.5 (p-value < 0.001). The overarching conclusion derived from this study is that interventions utilizing literacy-based play are efficacious in improving language skills in early childhood.